Changes to virus taxonomy and the Statutes ratified by the International Committee on Taxonomy of Viruses (2020) - Walker, Peter J.; Siddell, Stuart G.; Lefkowitz, Elliot J.; Mushegian, Arcady R.; Adriaenssens, Evelien M.; Dempsey, Donald M.; Dutilh, Bas E.; Harrach, Balázs; Harrison, Robert L.; Hendrickson, R. Curtis; Junglen, Sandra; Knowles, Nick J.; et al. (Archives of virology, 2020)
This article reports the changes to virus classification and taxonomy approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in March 2020. The entire ICTV was invited to vote on 206 taxonomic proposals approved by the ICTV Executive Committee at its meeting in July 2019, as well as on the proposed revision of the ICTV Statutes. All proposals and the revision of the Statutes were approved by an absolute majority of the ICTV voting membership. Of note, ICTV has approved a proposal that extends the previously established realm Riboviria to encompass nearly all RNA viruses and reverse-transcribing viruses, and approved three separate proposals to establish three realms for viruses with DNA genomes.